Photoinactivation of various antibiotic resistant strains of Escherichia coli using a paint coat - Vera M. Sousa (2013)
Multi-antibiotic resistant bacteria have been implicated with a large number of hospital-acquired infections and become one of the most significant concerns in public health. Given the potential risk of indoor transmission of these organisms in health care units, the development of a disinfection surface is highly attractive. Based on the recognized effectiveness of photocatalysis on the inactivation of microorganisms, a photocatalytic water born paint coat (UV-A/TiO2 - 10 W m(-2)) was assessed for its antibacterial action. The UV-A/TiO2 cellular inactivation is based on the production of reactive oxygen species (ROS). On the other hand, increased tolerance to the stress imposed by ROS has been reported to be associated with the acquisition of antibiotic resistance. Therefore, the bactericide activity of the photocatalytic paint coat was assessed with susceptible and multi-antibiotic resistant Escherichia coil strains of different phylogenetic lineages. For comparison purposes, the antimicrobial activity of the photocatalyst was assessed also in suspensions. Viability losses above 98.7% and 99.5% after 40 min of 10 W m(-2) UV-A exposure were recorded for cells contacting the surface of the photocatalytic paint coat and in suspension, respectively. No significant differences in the viability loss were found among the environmental tested strains, indicating that neither antibiotic resistance phenotype nor phylogenetic lineage influences the bacterial action of the photocatalyst. Results demonstrated that the photocatalytic action of the paint coat developed was effective against multi-antibiotic resistant E. coli strains. This technology has therefore potential to provide a powerful tool in the fight against the transmission of nosocomial infections.